2019
DOI: 10.1007/s12062-019-09245-7
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of Health Inequality Among the Elderly in Ghana

Abstract: In Ghana, the ageing population is growing at a fast pace amidst challenging socioeconomic environment. As such, the health of elderly persons in Ghana is of emerging concern and of high priority to the Government. In this study, we seek to measure health inequality among elderly persons in Ghana to determine its existence and explore the factors driving it. Data for the study were drawn from the World Health Organization (WHO)'s Study on Global Ageing and Adult Health (SAGE Wave 1) and analyzed using STATA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…Age was a significant factor associated with self-reporting poor health, showing a higher prevalence among individuals aged ≥70 (23.61%) compared to those in the younger group (60–69 years). This finding aligns with the existing literature indicating an increasing prevalence of poor health with increasing age [ 28 , 31 , 32 ]. For instance, a study in Brazil found an association of age with mortality in older men, with each additional year increasing the risk of death by 5% [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Age was a significant factor associated with self-reporting poor health, showing a higher prevalence among individuals aged ≥70 (23.61%) compared to those in the younger group (60–69 years). This finding aligns with the existing literature indicating an increasing prevalence of poor health with increasing age [ 28 , 31 , 32 ]. For instance, a study in Brazil found an association of age with mortality in older men, with each additional year increasing the risk of death by 5% [ 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…The likelihood of reporting a poor health status was also lower among those with health insurance compared to those without insurance in the logistic regression. Although Fonta et al [ 28 ] found no significant difference in SRH between insured and uninsured older individuals, Kunna et al [ 4 ] emphasized that the absence of health insurance coverage contributed to approximately 12% of observed health inequalities. Therefore, in addition to old age being a predisposing factor for poor health, access to health insurance is an important consideration for governments to enhance the health situation of the older population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If there is a competitive relationship between age and SES when they have impacts on health inequality, we need to focus more on the health status of the elderly with low SES [24]. Fonta’s study on health inequality among the elderly in Ghana found the same conclusion: the poor suffer more health inequalities [25].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the poor have limited access to health services resulting in poor health outcomes. 24 In 2019, Ghana in its quest to achieve the SDGs in health developed a roadmap to guide implementation of the Universal Health Coverage (UHC). This seeks to reduce financial barriers to health care, improve health care financing, and strengthen the health care system for equitable access by the citizenry.…”
Section: Introductionmentioning
confidence: 99%